Tuturan Ekspresif dan Direktif dalam Pementasan Teater Berjudul 'Yang Paling Manusia' Karya SMAN 4 Sidoarjo - Kusuma Wardani, Paramita; Fatimatuz Zahro, Nanda; Jauhari, Falah; Naila Shofa, Anindha; Fahman Alkahfi, Achmad; Mushoffa, Zuyyinatul; Purwo Yudi Utomo, Asep (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The general and specific important issues encountered in this article are the discussion of pragmatics, expressive and directive speech acts in theater performances. Expressive and directive speech acts often have complex pragmatic functions, for example, commands that are conveyed indirectly or expressions that contain implicit meanings. is to explore the understanding of the function, meaning, and impact of language use in communication, especially in drama scripts or theater performances. The research method used in this research is descriptive qualitative. The data source in this research is speech acts contained in the video of the theater performance entitled “The Most Human” by SMAN 4 Sidoarjo. The data in this study are fragments of pragmatic discourse contained in the video of the theater performance. In this study, it can be concluded that there are 19 data of expressive speech acts and 25 data of directive speech acts in the theater performance video entitled 'The Most Human' by SMAN 4 Sidoarjo. The functions found in expressive speech acts include 6 advice data, 6 rejection data, 3 motivation data, 1 pride data, 2 concern data, 4 satire data, and 2 affection data. Meanwhile, there are 3 types of functions in directive speech acts, namely 9 data of advising, 11 data of asking, and 5 data of criticizing.